DETEKSI AGLUTINASI SECARA OTOMATIS UNTUK UJI GOLONGAN DARAH TIPE ABO BERBASIS KERTAS - Handono, Juli; Wijaya, Sastra Kusuma; Ibrahim, Anwar Soefi (Universitas Pelita Harapan, 2017)
ABSTRACT. The research is the early study of development of automatic detection for the paper-based agglutination devices as a determinant of ABO blood typing, namely the integration of the blood type test equipment based on paper chromatography and forward grouping method with agglutination detection through image processing. Paper test was made by Whatman No. 4 filter paper with three hydrophilic columns, the paper test pattern were printed by using laser printers and cutting process to make hydrophobic field, paper test printed were placed in waterproof cases that was printed with a 3D printer. Reagents anti-A, anti-B and Anti-D (rhesus) were immobilized on each hydrophilic columns. By measurement of optimization paper strips obtained the value of optimization volume of reagents immobilized and optimization of blood volume test, each 6 µl Anti-A, Anti-B and Anti-D were immobilized on hydrophilic columns and 40 µl amount of blood sample needed for testing. The preliminary study was produced image processing software for blood agglutination detection with Absolute Subtract Difference (ASD) method, it was designed to support single-board computer Raspberry Pi and mini camera for decision result of blood type on the display. The test results get a high accuracy by comparing the results with slide test method.